Detection of Serum Antibody Levels Against Infectious Bursal Disease (IBD) Virus Using Indirect Hemagglutination (IHA) Test in Commercial Broilers - I., Hussain; Zahoor, M.A.; Rasool, M.H.; Mahmood, M. Shahid; Mansoor, M.K.; Riaz, M.N. (International Journal of Poultry Science, 2003)
A total of 336 Serum samples were collected from different commercial broiler farms and slaughter shops from in and around Faisalabad. These samples were divided in to three groups according to the age of the birds i.e. 0-3 weeks (86 samples), 3-6 weeks (68 samples) and 6-8 weeks (182 samples). Indirect hemagglutination (IHA) test was used to titrate the serum antibodies against infectious bursal disease virus. Hyper immune serum was raised in laboratory rabbits against IBDV vaccine (D-78). It was used to identify and confirm the IBD virus from bursal tissues isolated from the IBD affected flocks using the qualitative tests i.e. agar gel precipitation and modified counter immuno-electrophoresis. The viral antigen was sonified and used to sensitize the Human "O" erythrocytes without any coupling agent. 1% sensitized erythrocytes suspension was prepared and used to determine the antibody titer. Results indicated that out of 336 test serum samples 221 (65.77%) were positive. The maximum positive samples belonged to 6-8 weeks of age (78.57%) followed by 3-6 weeks (60.29%) and 0-3 weeks (43.02%), respectively. Calculated geometric mean titers for groups 0-3, 3-6 and 6-8 wks of age, were found to be 6.37, 10.84 and 16.14, respectively.